HISTORICAL AND THEORETICAL BASIS OF THE ESTABLISHMENT AND DEVELOPMENT OF VOLUNTEERING - ГУК, Ольга (Київський національний університет імені Тараса Шевченка, 2025)
Background. The article is devoted to the study of the historical and theoretical foundations of the formation and development of volunteerism. Today, volunteers play a key role in providing assistance when society has to face a number of difficulties (war, natural disasters, epidemics, etc.). Results. It is substantiated that volunteering is one of the elements of civil society, the development and study of which has recently received the attention of the state. It was determined that volunteering is a wide range of activities, including traditional forms of mutual and self-help, official provision of services and other forms of civic participation, carried out voluntarily for the benefit of the general public without expectation of monetary reward. It is argued that volunteering is a voluntary activity chosen consciously by a person and which does not pursue commercial gain. Volunteering is a manifestation of public activity and civic responsibility. The study is devoted to the analysis of volunteering in Ukraine from the point of view of the historical development of this phenomenon. The importance of the study is due to the fact that national volunteering in Ukraine requires appropriate scientific analysis. It is worth noting that an important aspect of volunteering is the systematization of experience and the determination of the specifics of the formation and functioning of the volunteer movement in Ukraine at the current stage. In the study, based on the study of historical and pedagogical sources, the study of state documents, general scientific methods of research (analysis, synthesis, generalization, systematization) were used on the issues of the formation and development of the volunteer movement. The specific features and main problems of the development of the volunteer movement in Ukraine are revealed. the terminological base of the phenomenon of volunteering is clarified; the reasons for the development and implementation of the laws of Ukraine regarding volunteer activities are given. Conclusіons. Volunteers help people in difficult life situations, support social projects and initiatives, ensuring an appropriate quality of life for various categories of the population

Вступ . Присвячена дослідженню історико-теоретичних засад становлення й розвитку волонтерства. Натепер волонтери відіграють ключову роль у наданні допомоги, коли суспільству доводиться стикатися з багатьма труднощів(війна, стихійні лиха, епідемії та ін.). Результати . Обґрунтовано, що волонтерство є одним із елементів громадянського суспільства, на розвиток і вивчення якого останнім часом звернено увагу держави. Визначено, що волонтерська діяльність – це широке коло діяльності, включаючи традиційні форми взаємодопомоги й самодопомоги, офіційне надання послуг та інші форми громадянської участі, що здійснюється добровільно на благо широкому загалу без розрахунку на грошову винагороду. Аргументовано, що волонтерство – це добровільна діяльність, обрана свідомо особою і яка не переслідує комерційної вигоди. Волонтерство – це прояв громадської активності та громадянської відповідальності. Дослідження присвячено аналізу волонтерської діяльності в Україні з погляду історичного розвитку цього явища. Важливість дослідження обумовлена тим, що національна волонтерська діяльність в Україні вимагає відповідного наукового аналізу. Варто зазначити, що важливим аспектом волонтерства є систематизація досвіду та визначення специфіки становлення і функціонування волонтерського руху в Україні на сучасному етапі. На основі вивчення історико-педагогічних джерел, вивчення державних документів використовувались загально-наукові методи дослідження (аналіз, синтез, узагальнення, систематизація) із питань становлення й розвитку волонтерського руху. Розкрито специфічні риси й основні проблеми розвитку волонтерського руху в Україні. З'ясовано термінологічну базу феномена волонтерства; наведено причини розробки і впровадження законів України щодо волонтерської діяльності.
ІСТОРИКО-ТЕОРЕТИЧНІ ЗАСАДИ СТАНОВЛЕННЯ Й РОЗВИТКУ ВОЛОНТЕРСТВА
Keywords: волонтерство; благодійність; особистість; доброволець; допомога; соціальні потреби; національний волонтерський рух; volunteering; charity; personality; volunteer; help; social needs; national volunteer movement